The Impacts of Strategic Improvisation in enhancing organizational sustainability An analytical study of the opinions of administrative leaders in a sample of oil and gas producing companies in the Kurdistan Region of Iraq - Nori, Range M.; Abdulla, Daroon Faridun; Qadir, Beston Muhammed (Sulaimani Journal for Humanities, 2023)
The aim of this study is to determine the impact of strategic improvisation through its dimensions (Strategic Vigilance, Strategic Agility, Minimal Structures, Solution building) In achieving organizational sustainability (economic, social, environmental and ethical sustainability) in oil and gas production fields in the Iraqi Kurdistan Region operated by oil and gas companies. The main problem of the study is the lack of organizational sustainability in the companies within the study. The Descriptive analytical method has been used to analyze the data and describe the variables and dimensions in the study. The study was conducted on eight oil and gas production companies that are currently in the process of extracting and producing oil and gas. Questionnaire form has been used as the data collection tool. The study population includes employees with responsibilities in the eight (8) oil and gas companies, which number (308) employees, these employees answered the questions, but the total number of forms distributed was (410) forms. Simultaneously and realistically, Statistical tools were applied software AMOS and IBM SPSS Amos 26. As a result of the data analysis, several results were obtained by describing and identifying both variables in the study, the most important of which is the existence of a direct and significant relationship between the dimensions of strategic improvisation and the dimensions of organizational sustainability. The dimension of the strategic improvisation variable also has had a positive impact on the organizational sustainability process in all the companies in the study framework. Finally, a number of recommendations for future research are proposed, the most important of which is that attention should be paid to the implementation of the study variables in all industrial sectors in Iraqi Kurdistan to solve some of the management problems. The originality of this study stems from the fact that it is the first time that these two variables have been combined and used in a study of the oil and gas management sector in the Iraqi Kurdistan Region.
Keywords: Strategic Improvisation; Organizational Sustainability; Oil and Gas Company; Kurdistan regional government